THE EFFECT OF VARIOUS PLANTING MEDIA ON THE GROWTH OF COCONUT SEEDLINGS (Cocos nucifera L.) AT THE NURSERY STAGE - Bella Dwi Safitra Br Milala; Octanina Sari Br Sijabat; Ali Ramadhan (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2026)
This study aimed to investigate the effect of various planting media mixtures and watering frequencies, as well as their interactions, on the growth of coconut seedlings (Cocos nucifera L.) during the nursery stage. The research was conducted in Medan Selayang, North Sumatra, Indonesia, from November 2025 to February 2026, using a factorial Randomized Block Design (RBD/RAK) with two factors: three types of planting media (P0: Cow Manure + Topsoil, P1: Goat Manure + Topsoil, P2: Chicken Manure + Topsoil) and three watering frequencies (A0: twice daily, A1: no watering, A2: once every two days). The measured parameters included plant height, stem diameter, and leaf count. The results showed that the planting media significantly affected plant height, stem diameter, and leaf count, with the best results obtained from P2 (Chicken Manure + Topsoil). Watering frequency also had a significant impact, with A2 (once every two days) producing the highest growth across all parameters. Additionally, the interaction between planting media and watering frequency significantly influenced plant growth, with the best combination being P2A2. This study highlights the importance of selecting the right planting media and watering regime for optimizing the growth of coconut seedlings.